Antibacterial Property of Cellulose Acetate Composite Materials Reinforced with Aluminum Nitride - Thefye P. M. Sunthar; Francesco Boschetto; Hoan Ngoc Doan; Taigi Honma; Kenji Kinashi; Tetsuya Adachi; Elia Marin; Wenliang Zhu; Giuseppe Pezzotti (MDPI AG, 2021)
Cellulose acetate (CA) is a synthetic compound that is derived from the acetylation of cellulose. CA is well known as it has been used for many commercial products such as textiles, plastic films, and cigarette filters. In this research, antibacterial CA composites were produced by addition of aluminum nitride (AlN) at different weight percentage, from 0 wt. % to 20 wt. %. The surface characterization was performed using laser microscope, Raman and FTIR spectroscopy. The mechanical and thermal properties of the composite were analyzed. Although the mechanical strength tended to decrease as the concentration of AlN increased and needed to be optimized, the melting temperature (Tm) and glass transition temperature (Tg) showed a shift toward higher values as the AlN concentration increased leading to an improvement in thermal properties. AlN additions in weight percentages >10 wt. % led to appreciable antibacterial properties against S. epidermidis and E. coli bacteria. Antibacterial CA/AlN composites with higher thermal stability have potential applications as alternative materials for plastic packaging in the food industry.